1076 CPAP And Bilateral Periorbital Edema: A Case Report. (12th April 2019) - Lixon, A; Pillai, M; Abdulfattah, O; Weinstein, M
Abstract: Introduction: Obstructive sleep apnea (OSA) has a prevalence of 22% (9–37%) in men and 17% (4–50%) in women. Continuous Positive Airway Pressure (CPAP) is the leading therapy presently in use for OSA. As the disease and the therapy became widespread, so has the emergence of side effects. One such adverse effect attributable to CPAP, albeit rare, is peri-orbital edema. Report of Case: A 59-year-old female presented for evaluation of bilateral eyelid swelling, which was noticed after two weeks of initiating treatment for severe OSA with CPAP at 16cm of water. Swelling subsided after she stopped using the CPAP for two days but returned once she resumed use. Further queries revealed that she was using a full face mask and swelling appeared after she began to tighten the mask to minimize air leaks. No past history of head trauma or facial bone fractures were reported. On examination she did not appear to be in distress, but had bilateral eyelid edema. There was no erythema, tenderness, subcutaneous emphysema or evidence of infection of the eyelids. The rest of the examination was unremarkable. ENT and Ophthalmology consultations were done and did not reveal any further pathology. Mask fitting was done in clinic and the full face mask was changed to Amara view mask without any leaks. She was able to continue using the CPAP with resolution of the periorbital swelling. Conclusion: Few cases of periorbital swellings have been reported after treatment with CPAP. A possible mechanism suggested is the obstruction to venous and lymphatic drainage leading to periorbital edema caused by tightening of the full face mask. Lower eyelid lymphatic's drain into the submandibular gland and upper eyelid lymphatic's drain into the parotid lymph nodes and compression of this passage can lead to edema above the level of obstruction. Review of the surface marking of lymphatic drainage and the point of contact of her full face mask suggested this could be the probable cause of the swelling. By switching to an amaraview mask this problem was overcome and the swelling resolved.